Kelayakan Sarana dan Prasarana Olahraga Prestasi di SMA Negeri se-Kabupaten Pemalang Tahun 2019 (Universitas Negeri Semarang, 2021)
ABSTRACT This problem of the research was sports facilities and infrastructure for achievement in SMA Negeri of Pemalang Regency were not yet known. This study aimed to determine the feasibility, completeness and condition of sports facilities and infrastructure achievements in SMA Negeri of Pemalang Regency in 2019. The problems was that exist in schools had not optimal in completing the inadequate of sports facilities and infrastructure. Things liked this hinder students who want to excel in non-academics. While sports facilities and infrastructure were important in supporting achievement with the complete of facilities and infrastructure, students could be more enthusiastic in carrying out sports activities. This research took the sampling of data sources was carried out purposively and snowball, the collection technique used triangulation (combined), the analysis was inductive / qualitative, and the results of qualitative researchers emphasized the meaning rather than generalization. Qualitative descriptive research with research methods used observation, interviews, and documentation. The population of this study used as many as 9 subjects of State Senior High Schools in Pemalang Regency. With the objects of sports facilities and infrastructure, the achievements in Public Senior High Schools of Pemalang Regency were: Running, Long Jump and Jump Jangkit, High jump, throw disc, throw javelin, reject bullets, badminton, table tennis, court tennis, basketball, volleyball, karate, taekwondo, silat. The data sources obtained from interviews with sports teachers / school authorities. The results showed that sports facilities and infrastructure in SMA Negeri of Pemalang Regency was not all schools provided facilities and infrastructure that were in accordance with the standards, but seen from the condition of sports facilities and infrastructure in schools, they were still fit for used for sports activities and were not harmful to students. For completeness, not all sports had the facilities and infrastructure in SMA Negeri of Pemalang Regency. Suggestions for this research were to be able to provided good things for the school to paid more attention to the completeness and feasibility of sports facilities and infrastructure in each sport for the sake of increasing sports performance, so that students or athletes could be more motivated in sports activities and be facilitated by not renting from outside or on the individual side. The school should further improve the management of existing sports infrastructure, so that they were more well maintained, for sports teachers to communicate a lot with the principal about the constraints of limited sports of facilities and infrastructure, and sports teachers should be more creative in dealing with the limitations of sports facilities and infrastructure.